Don't Say A Word: Angelhart Investigations # 2 - Brennan, Allison ([Place of publication not identified] : Mira Books, 2025)
"The police ruled Elijah Martinez's death an accidental drug overdose, but the teen's grieving mother isn't convinced. With the case officially closed, Angelhart Investigations is the only one who can help her find the truth. Margo Angelhart's sure this will be an easy solve--she'll talk to Elijah's friends and employer, retrace his steps, and figure out what happened in his final hours. Except none of his friends believe he did drugs, and the teacher who's been vocal about the police mishandling the case turns up dead. Every thread Margo pulls leads back to a dangerous drug ring that once ran through the school. When Margo's brother Jack, a former cop, can't get straight answers out of the police, they don't know if it's because of an active case--or a cover-up. Margo's only sure of one thing--she has to find out what really happened to Elijah before more teens become pawns in a twisted scheme"--.
new book 2025 fall.
Keywords: Death; Investigations; Drug traffic; Women private investigators; Mystery and Detective